Intelligent Multimedia Accessibility in Smart Environments Using IoT and Multi-Viewpoints Modeling - Bettou, Farida; Boulkroun, Bouchra; Boudjit, Abdelhamid (International Journal of Interactive Mobile Technologies (iJIM), 2026)
Smart and mobile devices have become essential for all users, including individuals with physical disabilities such as deafness, blindness, or other impairments. This work proposes a novel approach that integrates two key technologies, the Internet of Things (IoT) and MultiViewpoints (MVP), to enhance and personalize the use of smart and mobile devices for people with physical disabilities. This approach enables real-time interaction and dynamic content adaptation. IoT is employed to enhance context-awareness, allowing smart devices to predict the user’s current context and deliver appropriately adapted content. In parallel, the MVP framework supports the development of MVP Ontology, which enables multi-perspective content analysis and personalized adaptation based on user viewpoints. The proposed architecture is designed to be both flexible and intelligent. It ensures a versatile and inclusive multimedia delivery system that can adapt to diverse real-world scenarios through four layers of the architecture. We demonstrate the feasibility and effectiveness of this approach through a practical system optimized for both smart TV and Android platforms. A comparative analysis between mobile devices and smart TVs highlights the unique strengths of each in terms of performance and resource management.